Amino Acid Profile of Rhus coriaria L. (Sumac) Grown in Different Regions - Ali, Haval Mohammed; Ozer, Dursun; Karatas, Fikret; Saydam, Sinan (Kahramanmaras Sutcu Imam Univ Rektorlugu, 2024)
In this study, the amounts of amino acids in Rhus coriaria L. (Sumac) samples grown in different regions were analyzed by High Performance Liquid Chromatography (HPLC). A comparison of the amino acid content of analyzed samples showed that Mara* sumac was the richest in glutamic acid, on the other hand, Kadana and Sheladize were rich in nonessential amino acids. It was observed that the sumacs of Shelaza and Mara* regions were the poorest for non -essential amino acids. In terms of essential amino acids, it was determined that the sumacs of the Kadana and Sheladize regions were richer, while the sumacs of the Suleymania and Mara* regions were poorer. It can be said that all of the examined sumac samples are rich in glutamic acid, histidine and alanine, but poor in glycine. It was seen that the richest in terms of total essential and non -essential amino acids was the Kadana sumac, while the poorest was the Shelaza sumac. It can be said that the amount of essential and non -essential amino acids varies between regions, resulting from geographical and ecological differences.
Keywords: Sumac; Rhus coriaria L.; Amino acids; HPLC